Der Fall Greifeld, Karlsruhe - Wissenschaftsmanagement und NS-Vergangenheit - Rusinek, Bernd-A (Veröffentlichungen aus dem Archiv des Karlsruher Instituts für Technologie, 2019)
This book examines the professional life of Rudolf Greifeld, who was a managing director from 1956 to 1974 at the Karlsruhe Nuclear Research Center. Main topics are his role in National Socialism and the allegations against him risen in the 1970s. The survey also includes Greifeld's colleagues in the management of the center, whose careers in National Socialism had progressed much further and in some cases had led to much stronger entanglements.